The Transcriptional Response of Candida albicans to Weak Organic Acids, Carbon Source, and MIG1 Inactivation Unveils a Role for HGT16 in Mediating the Fungistatic Effect of Acetic Acid. Issue 11 (1st November 2017) - Cottier, Fabien; Tan, Alrina Shin Min; Yurieva, Marina; Liao, Webber; Lum, Josephine; Poidinger, Michael; Zolezzi, Francesca; Pavelka, Norman
Abstract: Candida albicans is a resident fungus of the human intestinal microflora. Commonly isolated at low abundance in healthy people, C. albicans outcompetes local microbiota during candidiasis episodes. Under normal conditions, members of the human gastrointestinal (GI) microbiota were shown to keep C. albicans colonization under control. By releasing weak organic acids (WOAs), bacteria are able to moderate yeast growth. This mechanism displays a synergistic effect in vitro with the absence of glucose in medium of culture, which underlines the complex interactions that C. albicans faces in its natural environment. Inactivation of the transcriptional regulator MIG1 in C. albicans results in a lack of sensitivity to this synergistic outcome. To decipher C. albicans transcriptional responses to glucose, WOAs, and the role of MIG1, we performed RNA sequencing (RNA-seq) on four biological replicates exposed to combinations of these three parameters. We were able to characterize the (i) glucose response, (ii) response to acetic and butyric acid, (iii) MIG1 regulation of C. albicans, and (iv) genes responsible for WOA resistance. We identified a group of six genes linked to WOA sensitivity in a glucose- MIG1 -dependent manner and inactivated one of these genes, the putative glucose transporter HGT16, in a SC5314 wild-type background. As expected, the mutant displayed a partial complementation to WOA resistance in the absence of glucose. This result points toward a mechanism of WOA sensitivity in C. albicans involving membrane transporters, which could be exploited to control yeast colonization in human body niches.